2022
DOI: 10.1002/ptr.7579
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid extract of saffron by‐product alleviates hyperuricemia via inhibiting xanthine oxidase and modulating gut microbiota

Abstract: Hyperuricemia was associated with the overproduction or inadequate excretion of uric acid, while its association with gut microbiota has emerged although few studies were focused on it. Previously, we have reported a flavonoid extract from saffron floral bio-residues lowered uric acid in potassium oxonate-induced hyperuricemic mice.In this study, the impacts of the flavonoid extract on potassium oxonate-induced hyperuricemic rats were evaluated through its effects on serum, renal, intestinal uric acid, and xan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Interestingly, the Hsp-Cu(II) complex showed a better uric acid lowering activity in vivo than many natural plant active ingredients. For example, anthocyanin extracted from purple sweet potato and flavonoid extracted from saffron had only 65.3% and 56.7% of the UA-lowering effect compared with Alp in vivo, respectively [36,56], while the reducing effect of the medium-dose Hsp-Cu(II) complex on serum UA was close to that of Alp, and the high-dose complex was better than that of Alp. At the same time, the complex returned the kidney tissue damage to a normal state in hyperuricemia mice, confirming the UA-lowering ability of the Hsp-Cu(II) complex.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, the Hsp-Cu(II) complex showed a better uric acid lowering activity in vivo than many natural plant active ingredients. For example, anthocyanin extracted from purple sweet potato and flavonoid extracted from saffron had only 65.3% and 56.7% of the UA-lowering effect compared with Alp in vivo, respectively [36,56], while the reducing effect of the medium-dose Hsp-Cu(II) complex on serum UA was close to that of Alp, and the high-dose complex was better than that of Alp. At the same time, the complex returned the kidney tissue damage to a normal state in hyperuricemia mice, confirming the UA-lowering ability of the Hsp-Cu(II) complex.…”
Section: Discussionmentioning
confidence: 97%
“…Amino acids could not only be metabolized into vital nitrogen-containing substances such as uric acid, urea, and ammonia that participated in the nitrogen cycle in the body but also promote the uric acid excretion in the urine, making it closely associated with the metabolic process of uric acid. , Numerous studies have reported that the imbalance of amino acid metabolism mediated by gut microbes is associated with HN. , HN could be accurately predicted by a combination of amino acid profiles, and the area under the curve was 1.00. In the current study, both Tax4Fun analysis and metabolomic analysis showed abnormal amino acid metabolism in HN rats, which coincided with the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…These substances significantly reduced serum tumor necrosis factor (TNF)-α, interleukin-1β (IL-1β), interleukin-6 (IL-6), interleukin-12(IL-12), UA, and BUN (p < 0.01), and protected chondrocytes from erosive damage. Chen et al (68) found a flavonoid extract in saffron (Crocus sativus). After treatment of HUA rats with this extract, on the one hand, serum UA, CR, and BUN levels were significantly reduced in HUA rats (p < 0.05), serum and liver XOD activities were inhibited, and serum TG and LDL-C levels were From the above summary of 14 common medicinal and food plant resources used in traditional medicine for the treatment of HUA in some Asian countries, it is easy to find that some plant extracts are, they can be used to treat HUA and prevent kidney inflammation by inhibiting XOD activity and lowering serum UA, CR, and BUN levels.…”
Section: Other Medicinal and Edible Plant Resourcesmentioning
confidence: 99%
“…These substances significantly reduced serum tumor necrosis factor (TNF)-α, interleukin-1β (IL-1β), interleukin-6 (IL-6), interleukin-12(IL-12), UA, and BUN ( p < 0.01), and protected chondrocytes from erosive damage. Chen et al ( 68 ) found a flavonoid extract in saffron ( Crocus sativus ). After treatment of HUA rats with this extract, on the one hand, serum UA, CR, and BUN levels were significantly reduced in HUA rats ( p < 0.05), serum and liver XOD activities were inhibited, and serum TG and LDL-C levels were significantly reduced ( p < 0.05).…”
Section: Medicinal Food Homologous Plant Functional Food That Can Red...mentioning
confidence: 99%